2012
DOI: 10.4240/wjgs.v4.i12.278
|View full text |Cite
|
Sign up to set email alerts
|

Non-steroidal anti-inflammatory drugs in colorectal surgery: A risk factor for anastomotic complications?

Abstract: In a recent article, Gorissen et al report on 795 patients with primary colorectal anastomosis operated on during the period 2008-2010 for different colorectal conditions at two centres. The leakage rate was significantly higher among patients who were administered non-steroidal anti-inflammatory drugs (NSAIDs) in the perioperative course. A dose-response relationship could also be traced, where longer NSAID use yielded a higher risk of anastomotic breakdown. However, as this study is observational in design, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…However, the authors categorised diclofenac as a nonselective NSAID, and it was also the most common substance in this category. This may have confounded and diluted the association between the different NSAIDs and the leakage risk, as their COX-2 selective substances included celecoxib and meloxicam, both sharing similar affinity to the COX enzymes as diclofenac [15,16,24] . However, any NSAID use was still a risk factor for leakage, which is in contrast to the current study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the authors categorised diclofenac as a nonselective NSAID, and it was also the most common substance in this category. This may have confounded and diluted the association between the different NSAIDs and the leakage risk, as their COX-2 selective substances included celecoxib and meloxicam, both sharing similar affinity to the COX enzymes as diclofenac [15,16,24] . However, any NSAID use was still a risk factor for leakage, which is in contrast to the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic inflammation is recognized as one of cancer hallmarks [ 37 , 38 ]. The relationship between inflammation and cancer is supported by the observation that prolonged use of nonsteroidal anti-inflammatory drugs (NSAIDs) is associated with reduced risk to developing various types of cancers [ 39 ]. With the setting of murine macrophage RAW264.7 cells experimental system, we showed that TFRG from RG effectively blocked LPS/IFN- γ -induced NO production and iNOS expression without cytotoxicity ( Table 1 ; Figures 1 and 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…As summarized in a review by Rushfeldt et al [4], three early clinical studies suggested that the cyclo-oxygenase-2 (COX-2)-selective NSAIDs diclofenac and celecoxib were associated with a 5-fold increase in the rate of anastomotic leaks when administered for postoperative analgesia [5][6][7]. These studies led to a growing interest in the possible adverse effects of NSAIDs on fresh intestinal anastomoses [8][9][10][11][12][13][14][15], and the question arose whether this was a class effect associated with the anti-inflammatory effect of NSAIDs in general, or whether the adverse effect was attributed to specific NSAIDs or subgroups of NSAIDs with a different COX selectivity [4,16,17]. As a consequence, if the anti-inflammatory effect per se was the reason for the anastomotic leaks, then the use of perioperative anti-inflammatory steroids should also be studied in a context with NSAID use.…”
Section: Introductionmentioning
confidence: 99%